Formation of ready for professional activity of future service favorites - Hevko, Ihor Vasilievich (Journal of Education, Health and Sport, 2020)
The article examines the readiness for professional activity of future specialists in the service sector, a certain systematic approach to training, which should become the basis for its modernization. In addition, appropriate mechanisms are needed to ensure that the system responds to environmental challenges. Vocational education is not just a means of obtaining and disseminating the necessary knowledge, but an essential factor in the adaptation of an individual in a constantly changing society. In the article it is proved that the sphere of services, in which professional competence - the ability to apply knowledge and skills for successful activity - becomes the main and determining factor - allows to successfully solve the actual tasks related to the motivation of the specialist of the sphere of services. The content of the professional training of specialists is defined in such component of the state industry standard as the educational and professional training program. Therefore, the analysis of the state of professional training of future specialists in the field of service in forming their readiness for professional interaction with service consumers shows that the practical training does not correspond to the requirements of employers, namely: insufficient ability to deal positively with conflict situations; uncertainty about professional activities.